Effects of preparation conditions on the ionic conductivity of hydrothermally synthesized Li1+xAlxTi2-x(PO4)3 solid electrolytes. (10th September 2015) - Kim, Kwang Man; Shin, Dong Ok; Lee, Young-Gi
Abstract: Li1+ x Al x Ti2- x (PO4 )3 (LATP) solid electrolytes are prepared by hydrothermal reaction as an effective method to yield moderate ionic conductivity adoptable in actual lithium-ion batteries. Particularly examined in this study are the effects of the synthesis conditions, such as Al dopant concentration ( x ), hydrothermal reaction time, and calcination and sintering temperatures, on the ionic conductivity of the synthesized LATP. Through repeated synthesis and characterizations of the LATPs by variation of the values of condition variables, the optimum condition for the best LATP with adequate ionic conductivity applicable to actual lithium batteries are determined to be x = 0.3 or 0.4, a hydrothermal reaction time of 12 h, and calcination and sintering temperatures of 600 °C and 900 °C, respectively.